Experimental performance evaluation of short duration high speed flow shock tunnel - Amir A.-F.; Yusoff M.Z.; Ahmed D.I.; Shuaib N.H. (2023)
This paper describes the experimental procedure to evaluate the performance of short duration high speed flow shock tunnel located at the Universiti Tenaga Nasional "UNITEN". The experimental work includes measurements of pressure, peak pressure, shock strength and shock speed. Physical description of the facility along with the principle of operation is presented. The pressure history of flow process was captured using fast response pressure transducer mounted at three stations located at the end of the facility. The measurements were performed using two different driver/driven gas combination. The first one is Air-Air while the second one was Helium-Air. The results of two combinations were compared and analyzed. The results show that the facility's performance is highly influenced the gas combination. The results provide very good estimate for the above mentioned parameters obtained after diaphragm rupture and also provide better understanding of the parameters that affect the performance of the facility. 2009 IEEE.